Prospects for the Use of Cannabinoids in Psychiatric Disorders - Graczyk, Michał; Łukowicz, Małgorzata; Dzierzanowski, Tomasz (Frontiers in Psychiatry, 2021)
Increasing evidence suggests an essential role of the endocannabinoid system (ECS) in the regulation of stress, mood, and psychiatric disorders, including anxiety and depression. The psychoactive effects of cannabis are described as euphoric, calming, anxiolytic, and sleep-inducing and positively affect the mood, but can also adversely affect therapy. The responses to cannabinoid medications depend on the patient's ECS activity, the proportion of phytocannabinoids, the terpenoid composition, and the dose used. THC and CBD may have opposing effects on anxiety. Current guidelines recommend caution in using THC in patients with anxiety or mood disorders. In a small number of clinical trials, cannabinoids used to treat cancer, HIV, multiple sclerosis, hepatitis C, Crohn's disease, and chronic neuropathic pain report decreases in anxiety or depression symptoms and presented sedative and anxiolytic effects. Several studies have investigated the influence of potential genetic factors on psychosis and schizophrenia development after cannabis use. THC may increase the risk of psychosis, especially in young patients with an immature central nervous system. There is limited evidence from clinical trials that cannabinoids are effective therapy for sleep disorders associated with concomitant conditions. There is growing interest in the use of cannabis as a substitute for alcohol and drugs, also in the context of the risks of opioid use (e.g., opioid-related mortality). In this narrative review of the recent evidence, we discuss the prospects of using the psychoactive effects of cannabinoids in treating mental and psychiatric disorders.